Developing The 7 Stages of Startup (The Maturity Level of Startup): The Concepts of Startup Development Methodology - Asih Rohmani; Indra Gamayanto; Titien S Sukamto (IJISTECH (International Journal of Information System and Technology), 2021)
The development of e-commerce is growing very fast and cannot stop; it changes various sides of human life. This change is a big challenge for everyone, and this is a condition that must occur so that everyone can carry out activities more effectively and efficiently. This research produces a few kinds of Startup classification and Customer Relationship Management (CRM) classification. Furthermore, it provides C=R.S2 formula, a formula for developing CRM, and S=H.I2.M formula, a formula for developing a Startup. These two formulas were eventually evolving into the seven stages of Startup (the maturity level of Startup), where the seven steps are the stages in developing a Startup, starting from the local level to the international level. These seven stages work so that the Startup founder can gradually understand what needs and how to develop it by focusing more on CRM. The results of this study are a framework to be able to implement the seven stages. This research results from previous studies' development: The Development of Innovative CRM E-Commerce: The Case of Blibli. Com.